Adaptations of Candida albicans for Growth in the Mammalian Intestinal Tract - Rosenbach, Ari (American Society for Microbiology, 2010)
Although the fungus Candida albicans is a commensal colonizer of humans, the organism is also an important opportunistic pathogen. Most infections caused by C. albicans arise from organisms that were previously colonizing the host as commensals, and therefore successful establishment of colonization is a prerequisite for pathogenicity. To elucidate fungal activities that promote colonization, an analysis of the transcription profile of C. albicans cells recovered from the intestinal tracts of mice was performed. The results showed that within the C. albicans colonizing population, cells expressed genes characteristic of the laboratory-grown exponential phase and genes characteristic of post-exponential-phase cells. Thus, gene expression both promoted the ability to grow rapidly (a characteristic of exponential-phase cells) and enhanced the ability to resist stresses (a characteristic of post-exponential-phase cells). Similarities in gene expression in commensal colonizing cells and cells invading host tissue during disease were found, showing that C. albicans cells adopt a particular cell surface when growing within a host in both situations. In addition, transcription factors Cph2p and Tec1p were shown to regulate C. albicans gene expression during intestinal colonization.